On the Flexibility of Borders between Public Reason and Collective Ignorance - Żardecka, Magdalena (Tematy i Konteksty, 2017)
The main theme of the paper is the issue of the foundations of social life. The author begins by outlining the tradition of the Enlightenment represented by Immanuel Kant, who attempted to justify rationally the basis of social life. Then she moves back to antiquity, to Plato, the sophists and Aristotle, to show their attitude towards the foundations of public life in order to briefly present in the following stage the original concept of Baruch Spinoza and, in more details, the views of Blaise Pascal, who is the main figure of this presentation. The final part of the paper includes a draft of the philosophical thought of postmodernism, represented by such intellectuals as Michel Foucault, Richard Rorty and Jürgen Habermas. The author additionally presents an exposition of the concept of habitus by Pierre Bourdieu, interpreting it accordingly to her previous reflections. The course of thought in these considerations intends to formulate a thesis which takes a stand against the most obvious opinion of Enlightenment, purporting that neither the contemporary liberal democracy nor people’s respect for it and their will to obey the law are founded on reason.